Dispositional middle constructions with accusative objects in Slovenian - Jakob Lenardič (Glossa, 2024)
This paper provides a study of an impersonal type of dispositional middle construction that appears in Slovenian. This impersonal construction atypically contains an undemoted thematic external argument in syntax, but nevertheless ascribes a disposition to the internal one in semantics, which goes against previous assumptions about the way in which syntax and semantics interact in middles. On the basis of this Slovenian construction, the paper develops a new syntactic and semantic analysis of the modal phrase whose head contributes the dispositional interpretation and assigns it to the internal argument. The paper shows how such an analysis accounts for both non-canonical Slovenian middles with syntactically realised external arguments as well as the more prototypical middles without external arguments both in Slovenian and English. Finally, the paper proposes why the external argument in the Slovenian impersonal middle is – exceptionally – not an intervener for the dispositional assignment.